Utilization of Social Media as a Tool for Learning Islamic Religious Education for Generation Z - Munawaroh; Kholid Musadad; Akhmad Khoiri; M. Supangat; Janiansyah Rani; Amanda Caprista (Yayasan Al Hidayah, 2026)
The development of digital technology has changed the paradigm of Islamic Religious Education (PAI) learning, especially for Generation Z, who are familiar with social media. This study aims to analyze the use of social media as a means of Islamic Religious Education (PAI) learning at IAI Darul Fattah Lampung and identify opportunities and challenges. The study used a descriptive qualitative approach with observation, interviews, and documentation techniques. The results show that YouTube, WhatsApp, Instagram, and TikTok are actively utilized in Islamic Religious Education (PAI) learning. YouTube is used to deliver video-based materials, WhatsApp as a communication and discussion medium, while Instagram and TikTok are used to reinforce Islamic values ​​through creative content. The use of social media increases student motivation, participation, and understanding and supports both synchronous and asynchronous learning. However, the study also identified challenges such as distraction from non-academic content, limited digital literacy among lecturers, and students' difficulty in selecting valid and moderate religious content. Therefore, targeted learning strategies and lecturer guidance are needed to make social media use more effective and educational for students.